Advances in Liposome-Encapsulated Phthalocyanines for Photodynamic Therapy - Rak, Jakub; Kabesova, Martina; Benes, Jiri; Pouckova, Pavla; Vetvicka, David (Life, 2023)
This updated review aims to describe the current status in the development of liposome-based systems for the targeted delivery of phthalocyanines for photodynamic therapy (PDT). Although a number of other drug delivery systems (DDS) can be found in the literature and have been studied for phthalocyanines or similar photosensitizers (PSs), liposomes are by far the closest to clinical practice. PDT itself finds application not only in the selective destruction of tumour tissues or the treatment of microbial infections, but above all in aesthetic medicine. From the point of view of administration, some PSs can advantageously be delivered through the skin, but for phthalocyanines, systemic administration is more suitable. However, systemic administration places higher demands on advanced DDS, active tissue targeting and reduction of side effects. This review focuses on the already described liposomal DDS for phthalocyanines, but also describes examples of DDS used for structurally related PSs, which can be assumed to be applicable to phthalocyanines as well.